A Crossover Randomized Controlled Trial of Priming Interventions to Increase Hand Hygiene at Ward Entrances - Schmidtke, Kelly Ann; Aujla, Navneet; Marshall, Tom; Hussain, Abid; Hodgkinson, Gerard P.; Arheart, Kristopher L.; Birnbach, David J.; Kudrna, Laura; Vlaev, Ivo (Frontiers in Public Health, 2022)
Abstract: Background. Research conducted in the United States suggests that two primes (citrus smells and pictures of a person’s eyes) can increase hand gel dispenser use on the day they are introduced in hospital. The current study, conducted at a hospital in the United Kingdom, evaluated the effectiveness of these primes, both in isolation and in combination, at the entry way to four separate wards, over a longer duration than the previous work. Methods. A crossover randomized controlled trial was conducted. Four wards were allocated for six weeks of observation to each of four conditions, including ‘control,’ ‘olfactory,’ ‘visual,’ or ‘both’ (i.e., ‘olfactory’ and ‘visual’ combined). It was hypothesized that hand hygiene compliance would be greater in all priming conditions relative to the control condition. The primary outcome was whether people used the gel dispenser when they entered the wards. After the trial, a follow up survey of staff at the same hospital assessed the barriers to, and facilitators of, hand hygiene compliance. The trial data were analyzed using regression techniques and the survey data were analyzed using descriptive statistics. Results. The total number of individuals observed in the trial was 9811 (female=61%), with similar numbers across conditions, including ‘control’ N=2582, ‘olfactory’ N=2700, ‘visual’ N=2488, and ‘both’ N =2141. None of the priming conditions consistently increased hand hygiene. The lowest percentage compliance was observed in the ‘both’ condition (7.8%), and the highest was observed in the ‘visual’ condition (12.7%). The survey was completed by 97 staff (female=81%). ‘Environmental resources’ and ‘social influences’ were the greatest barriers to staff cleaning their hands. Conclusions. Taken together, the current findings suggest that the olfactory and visual priming interventions investigated do not influence hand hygiene consistently. To increase the likelihood of such interventions succeeding, future research should focus on prospectively determined mechanisms of action.